Integrated gut microbiome and metabolomics analysis reveals microbial-metabolic cross-talk in allergic rhinitis - Sun, Guangchen; Zhao, Shouyan; Huang, Hehua; Guan, Wenchao; Wang, Xinzhuo; Zhang, Hong; Zhang, Min; Hou, Denghan; Xu, Chong; Chai, Ruonan (Frontiers in Microbiology, 2025)
BackgroundEmerging evidence indicates a link between gut dysbiosis and allergic rhinitis (AR) pathogenesis. Nevertheless, the mechanistic role of gut microbiota in AR progression requires further characterization. To address this, we employed an integrated multi-omics strategy to delineate gut microbial composition and metabolic signatures in AR patients.MethodsFecal specimens from 23 AR patients and 15 matched healthy controls (total n = 38) were subjected to 16S rRNA gene sequencing to assess bacterial community structure, alongside untargeted metabolomic profiling of microbial metabolites. Spearman’s rank correlation analysis was applied to evaluate microbiota-metabolite interactions.ResultsAllergic rhinitis patients exhibited altered gut microbial community structure (beta diversity, P < 0.05) with depletion of SCFA-producing genera such as Faecalibacterium and enrichment of pro-inflammatory taxa like Fusobacterium. Metabolomic profiling identified significant disturbances in pathways including pantothenate and CoA biosynthesis, glycolysis, and pyruvate metabolism. Key discriminatory metabolites included maltol and 4-coumaric acid. Integrative analysis revealed significant correlations between specific bacteria and metabolites, such as Faecalibacterium with D-phenyllactic acid (ρ = 0.515, q = 0.046).ConclusionOur findings demonstrate that AR is associated with gut dysbiosis and metabolic dysfunction, highlighting the role of microbial-derived metabolites in immune regulation via the gut-nose axis. These insights support the potential for microbiota-targeted therapeutic strategies in AR management.